A review of circular RNAs in colorectal cancer: insights into biomarker discovery and therapeutic targeting - Nambidi, Sibin; Shruthi, Karunakaran Bhuvaneswari; Kanimozhe, Sujatha Padmanaban; Banerjee, Antara; Kondaveeti, Suresh Babu; Duttaroy, Asim K.; Pathak, Surajit (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is one of the most common cancers, with an incidence that has increased significantly over the last 20 years. The World Health Organization (WHO), under its cancer program, identifies CRC as the third most prevalent cancer worldwide with a high mortality rate, especially in patients under the age of 50. Despite advances in surgery, chemotherapy, radiotherapy, and molecular targeted therapy, CRC shares a low survival rate and poor prognosis due to late diagnosis. To address these challenges, research into alternative diagnostic and therapeutic strategies has increasingly focused on molecular mechanisms, including noncoding RNAs (ncRNAs). Circular RNAs (circRNAs), a subclass of endogenous ncRNAs characterized by their covalently enclosed loop structure, demonstrate greater stability than linear RNAs, making them potential candidates for clinical applications. The circRNAs possess differential expressions in cancers and function as tumor suppressive or oncogenic activities. This review discusses the recent findings on circRNAs and their potential for biomarkers and therapeutic targets in CRC. As circRNAs can serve as miRNA sponges, increase or decrease mRNA expression, and function to regulate an oncogenic or tumor suppressor pathway, there may be the possibility for an early diagnosis, prognosis, or therapeutic role of circRNAs in CRC. Highlighting the clinical implications of circRNAs, this review discusses their potential to transform current CRC management strategies and address critical gaps in timely diagnosis and effective treatment. It also emphasized the need for further clinical research to validate their utility and translate these findings into practice.